Penerapan Uang Paksa Sebagai Bentuk Perlindungan Hukum Bagi Pihak Yang Dirugikan Atas Wanprestasi Dalam Perjanjian Sewa Menyewa Tanah - Sari, Gusti Ayu Widiastiti; Anak Agung Ayu Intan Puspadewi; Anak Agung Ayu Ngurah Sri Rahayu Gorda; I Gede Agus Kurniawan (Consensus : Jurnal Ilmu Hukum, 2025)
The purpose of this study is to examine how coercive fines, or dwangsom, are used as legal guarantees for parties who suffer losses due to breach of contract in land lease agreements. Land leases are civil law arrangements that can give rise to disputes, especially when one party fails to fulfill its obligations, such as paying rent after the agreed time or refusing to vacate the leased property after the lease term ends. In such circumstances, even though the court has issued a ruling, its implementation is often hampered by the absence of an effective enforcement mechanism. Therefore, dwangsom becomes an important instrument to ensure compliance with the judge's ruling through financial pressure on the defaulting party. This study uses a literature review method by examining primary, secondary, and tertiary legal materials, such as the Civil Code (KUH Perdata), Civil Procedure Regulations (RV), court decisions, scientific journals, and other legal literature. The analysis is conducted normatively by understanding the relevance and effectiveness of dwangsom in the Indonesian civil law system. The results of the study show that the application of dwangsom serves as a means of coercion so that court decisions can be implemented voluntarily and in a timely manner, thereby ensuring that the rights of the aggrieved party are fully protected. In addition, the application of dwangsom needs to be integrated with the principle of legal certainty in land administration to prevent disputes through clear registration and recording of rights.